Penerapan Model Blended Learning untuk Meningkatkan Keterampilan Mendengarkan pada Pembelajaran Bahasa - Firda Novialita; Indah Ekiyanti L; Farida Rahmania; Abd Aziz; Arif Syarifudin; Siti Aminah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Listening skills serve as a fundamental foundation in the teaching and learning process. This is because listening skills support the development of critical thinking and the ability to adapt to various life situations. One instructional model that can foster these abilities is the Blended Learning model. The aim of this study is to describe the steps, strengths, and weaknesses of implementing the Blended Learning model in language learning at Madrasah Tsanawiyah Negeri 1 Klaten Regency. This study employs a qualitative research approach. The research subjects are teachers at Madrasah Tsanawiyah Negeri 1 Klaten, with language teachers as the primary informants. Data collection techniques include interviews, observations, and documentation. The findings of this study are as follows: 1) The steps of the Blended Learning model include identifying learning objectives, designing a combination of face-to-face and online learning, selecting appropriate media and digital platforms, implementing instruction in rotation or integration, and conducting evaluation and reflection on learning outcomes. This model enables students to enhance their listening skills; 2) The advantages of the Blended Learning model include greater flexibility in time and learning location, increased interaction between students and teachers, and the potential to support student-centered learning; 3) The weaknesses of the Blended Learning model are the need for adequate technological infrastructure, the fact that not all teachers and students are digitally prepared, and the challenge of designing an effective integration between online and face-to-face instruction. The conclusion of this study is that the Blended Learning model can be implemented in the teaching and learning process as an effort to improve listening skills at the Madrasah Tsanawiyah or lower secondary school level.